Education Of A Boy Raised In A One-Step Family - N.Qodirjonova; O.Avezov (Zien Journals, 2024)
This article presents thoughts and opinions about the upbringing, psychology and behavior of boys raised in single-parent families.
Keywords: Society; children; upbringing; psychology